2023
DOI: 10.1186/s12888-023-04798-6
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, depression and post-traumatic stress disorder in patients on hemodialysis in the setting of the pandemic, inflation, and the Beirut blast: a cross-sectional study

Abstract: Background In 2020, Lebanon has witnessed its worst economic crisis, exacerbated by the COVID-19 pandemic and a massive explosion of its capital. Amidst these stressors, this study aims at assessing the prevalence of depression, anxiety, suicidality, post-traumatic stress disorder (PTSD) and cognitive impairment in patients undergoing hemodialysis in an academic hospital destroyed by the explosion. Methods This cross-sectional study conducted 6 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…The current study found that during COVID-19 pandemic, hemodialysis patients in Palestine had high levels of death anxiety and depressive symptoms as 69.8% of the sample reported death anxiety, and 66.2% reported depressive symptoms. Similarly, Ghiasi et al ( 25 ) found that 60.4% of the patients had high levels of death anxiety in Iran and in Lebanon, Khoury et al ( 45 ) reported a high rate of depression in patients on hemodialysis (57.1%). In addition, Duru ( 46 ) revealed that rates of depression were significantly higher both before and after COVID-19 pandemic in Turkey (63.1% vs. 75.0% as overall, and 19.0% vs. 33.3% for moderate-to-severe depression).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The current study found that during COVID-19 pandemic, hemodialysis patients in Palestine had high levels of death anxiety and depressive symptoms as 69.8% of the sample reported death anxiety, and 66.2% reported depressive symptoms. Similarly, Ghiasi et al ( 25 ) found that 60.4% of the patients had high levels of death anxiety in Iran and in Lebanon, Khoury et al ( 45 ) reported a high rate of depression in patients on hemodialysis (57.1%). In addition, Duru ( 46 ) revealed that rates of depression were significantly higher both before and after COVID-19 pandemic in Turkey (63.1% vs. 75.0% as overall, and 19.0% vs. 33.3% for moderate-to-severe depression).…”
Section: Discussionmentioning
confidence: 91%
“…In addition, Duru ( 46 ) revealed that rates of depression were significantly higher both before and after COVID-19 pandemic in Turkey (63.1% vs. 75.0% as overall, and 19.0% vs. 33.3% for moderate-to-severe depression). The Beck Depression Inventory scale and repeated exposure to traumatic war-zone conflicts or events have been suggested as possible explanations for the higher rates in these studies ( 45 ). Therefore, it is critical to assess depression and death anxiety in these patients because they have been linked to poor survival rates, a high risk of suicidal ideation, and non-adherence to therapy ( 47–49 ).…”
Section: Discussionmentioning
confidence: 96%
“…In association with the biochemical changes, ESRD patients frequently experience physiosomatic symptoms, including chronic fatigue, fibromyalgia, muscular pain, insomnia, headache, cognitive impairments, and affective symptoms, including depression and anxiety (Cohen and Kimmel, 2018, Savitha et al, 2020, Elzeiny and El-Emary, 2023, Ibrahim et al, 2023, Semaan et al, 2018, Qawaqzeh et al, 2023, Khoury et al, 2023, Burdelis and Cruz, 2023, Molfino et al, 2023, Asad et al, 2023. Previous studies showed a high incidence of chronic fatigue (42-89%) and depressive or/and anxiety symptoms (around 50%) in chronic renal disease (Kim et al, 2012, Yoong et al, 2017 (Artom et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The cognition and memory, psychological, and physical aspects of the quality of life of these patients deteriorate at an alarming rate [ 4 , 5 ]. Some hemodialysis patients develop dementia, anxiety, depression, and suicidal tendencies [ 6 ]. Furthermore, kidney function and cognitive power decrease considerably after 50 years of age [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%